Novel Potential of Effective Microorganisms as Bioattractant of Domestic Cockroaches in Malaysia. Issue 1 (2012) - Chan, Giek Far; Wong, Ling Lit; Rashid, Noor Aini Abdul; Othman, Fahmi
No abstract available